Oral Administration of Alginate Oligosaccharide from Padina sp. Enhances Tolerance of Oxygen Exposure Stress in Zebrafish (Danio rerio) - Ervia Yudiati; Rustadi Rustadi; Fanny Iriany Ginzel; Jelita Rahma Hidayati; Mila Safitri Rizfa; Nuril Azhar; Muhammad Salauddin Ramadhan Djarod; Eny Heriyati; Rabia Alghazeer (Marine Science Department Diponegoro University, 2020)
Alginate is rich in bioactive compounds and has been known to act as a stimulator on the innate immune system. The objective of this study is to determine polysaccharide and oligosaccharide alginate yield, that percentage inhibition with a different type of extraction, to evaluate growth performance as well as immune response by oxygen stress tolerance. Thermal heating with oven laboratory at 140oC for 4.5 hr was done to breakdown the polysaccharide into oligosaccharide. The extraction was conducted by maceration, filtration, precipitation, and centrifugation. Factorial design with two factors was implemented to 260 Zebrafish and reared in thirteen aquariums (20 fish per aquarium) for 12 days. Zebrafish was fed at different dose (4.0g; 6.0g; 8.0g.kg-1) and different type of extraction [noEDTA/noKCl; KCl; EDTA and (EDTAandKCl)]. The evaluation of radical scavenging activity was done spectrophotometrically at 515 nm. Results showed that the highest alginate yield either polysaccharide or oligosaccharide was gained from KCL treatments, percentage inhibition (82.61%), growth performance as well as tolerance of stress (P<0.05). The best growth performance was reached in oligosaccharide supplementation at 6.0g.kg-1 treatment. It can be concluded that alginate oliogosaccharide produced by thermal heating enhanced the antioxidant activity, boost the fish’s immune system, proofed by better growth performance and more tolerant to the low oxygen stress.